Dynamic Streching Socialization of Basketball Together with Indonesian Basketball Association of Bangkalan Regency at Elementary School Keraton 3 - Heni Yuli Handayani (Performa, 2019)
Basketball in Bangkalan Regency is still constrained in its development, especially at an early age level. At the early age level elementary schools become one of the agencies expected to play a high role in their development through both intracuricular and extracurricular activities in accordance with applicable curriculum regulations. In fact, none of the primary schools in Bangkalan Regency have a standard or minimum basketball court that suits the needs of young children in recognizing basketball games as stated in the basic competencies of big ball games. Conventional strategies used by teachers and sports extracurricular coaches in primary schools have resulted in monotonous and boring training models or basketball learning as suggested by the partners, namely PERBASI Bangkalan Regency. Through a small game of basketball it is hoped that it can be integrated with the introduction of basketball in early childhood in elementary school even with limited facilities and infrastructure as well as providing the latest knowledge in dynamic streching in early childhood in the form of active and passive heating that can be applied in introducing basketball to early childhood at the elementary school level. A total of 5 small basketball games, namely Tiggy line, Dribble Knockout, Team Dribble Relays (Speed ​​Dribble & Ball Handling), 4 Pass to Score, Bull in the ring. The five types of small games in Dynamic Streching for early childhood are expected to be a way out to be able to introduce basketball to early childhood in elementary school with a pleasant variation so as to avoid boredom students. Keywords: Socialization, Streching, Small Game, Basketball, Early Childhood, Elementary School.